ANALYSIS OF THE CAUSES OF THE UNITED STATES TRADE WAR WITH CHINA IN THE ERA OF ECONOMIC GLOBALIZATION - Mohammad Choirul Anam (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
To understand the trade war between the United States (US) and China, it is important to first discuss the underlying causes of the trade conflict. This paper mainly studies the main causes of the US-China trade war. By reviewing and analyzing the literature on China's economic development and the evolution of US-China relations, by comparing the impact of globalization on the US and China, and by exploring what can be learned from the US-Japan trade conflict to understand the current US-China situation. trade relations, research shows that there are three main forces triggering the US-China trade war. With different levels of importance, the three forces are globalization, different development strategies, and President Trump's political declarations. Through research proves that the US-China trade war is unavoidable under the recent geopolitical landscape